The Evaluation of Tourism in Turkey in Terms of Inflation - Şerife Yazgan Pektaş; Kurban Ünlüönen (Journal of Tourismology)
The purpose of this study is to reveal the relationship between inflation and tourism performance in Turkey using descriptive analysis. In the study, consumer price index (CPI) was examined in the light of numbers of tourist arrivals between 2004 and 2018, tourism income, average spending per person, average overnight stays, and inflation. Data was gathered from the Turkish Statistical Institute (TSI) and the Central Bank of the Republic of Turkey (CBRT). It was determined that inflation rises regionally in the tourist season because tourism has a seasonal characteristic. Our study shows that inflation was the highest between 2004 and 2018 and that although tourism demand increased in 2017 and 2018, tourism income, average spending per person and the number of average overnight stays decreased. In addition, it may be said that the amount of average spending per person by foreign tourists also decreased. In this case, it should be taken into consideration that not only inflation but also factors such as the global economic crisis, the fact that tourists who spend little (apart from on accommodation) prefer Turkey, and the fact that tourists do not have enough information about available tourist products affected the results of this study.